The Effect of Intellectual Capital, Industry Experience on the Application of Financial Accounting Standards in the Tourism Industry in Ambon City - Situmeang, Mis Fertyno; Latuamury, Sherlie Evabioni (Eastasouth Institute, 2023)
This research study investigates the effect of intellectual capital and industry experience on applying financial accounting standards in the tourism industry. This research focuses specifically on the Ambon City context, aiming to provide insight into the factors that shape financial accounting practices in the local tourism sector. A quantitative approach involved collecting data from 150 entrepreneurs in Ambon City and analyzing the data with the help of SPSS version 25 software. The quantitative phase involved distributing survey questionnaires to tourism industry stakeholders. The research findings indicate a positive correlation between intellectual capital, industry experience, and practical application of financial accounting standards. Further regression analysis confirms the significant impact of intellectual capital and industry experience on compliance with financial accounting standards. This research highlights the importance of collaboration, knowledge sharing, and continuous professional development in promoting effective financial accounting practices. These findings have important implications for policymakers, industry practitioners, and researchers, who emphasize the need to invest in developing intellectual capital, fostering industry experience, and promoting collaboration within the tourism industry. Ultimately, this research contributes to an understanding of the dynamics between intellectual capital, industry experience, and application of financial accounting standards.